Internet, mail, and mixed-mode surveys the tailored design method - Dillman, Don A. 1941-2024; Smyth, Jolene D.; Christian, Leah Melani (Wiley, 2009)
Contents: Turbulent times for survey methodology -- The tailored design method -- Coverage and sampling -- The basics of crafting good questions -- Constructing open- and closed-ended questions -- From questions to a questionnaire -- Implementation procedures -- When more than one survey mode is needed -- Longitudinal and internet panel surveys -- Customer feedback surveys and alternative delivery technologies -- Effects of sponsorship and the data collection organization -- Surveying businesses and other establishments -- Coping with